2013
DOI: 10.1080/20932685.2012.753337
|View full text |Cite
|
Sign up to set email alerts
|

The concept of creative collaboration applied to the fashion industry

Abstract: Co-branding is an interesting approach to building differentiation and reputation. In the fashion industry, one well-known example of co-branding is the creative collaboration between fashion designers and mass-market retailers. This paper aims to explore this specific example of co-branding. It first introduces the concept of co-branding and presents its application by the Swedish retailer H&M. An exploratory study with a convenience sample confirms the interest of the approach. Further analysis of the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…A recent successful example is the limited-edition collaboration between Target and Lilly Pulitzer. This collaboration attracted extensive media attention and caused great excitement among consumers (Grinberg, 2015;Kunde, 2012;Rollet et al, 2013) with products selling out within hours of their release in stores (Grinberg, 2015). Items went quickly online as well; shoppers reported that their items in their carts disappeared by the time they were ready to check out (Grinberg, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent successful example is the limited-edition collaboration between Target and Lilly Pulitzer. This collaboration attracted extensive media attention and caused great excitement among consumers (Grinberg, 2015;Kunde, 2012;Rollet et al, 2013) with products selling out within hours of their release in stores (Grinberg, 2015). Items went quickly online as well; shoppers reported that their items in their carts disappeared by the time they were ready to check out (Grinberg, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study offers several important theoretical implications. Although brands are increasingly offering co-brands with restricted time duration (Ginman et al , 2010; Nabec et al , 2016; Rollet et al , 2013; Wang et al , 2015), very few studies have been conducted to understand the effectiveness of this brand and retailer co-brand strategy. Research on company growth strategies has predominately focused on line or brand extensions exclusively (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived fit, also known as coherence, between brand parties is critical (Rollet et al , 2013; Simon and Ruth, 1998). In fact, perceived fit is thought to be the most important factor that determines a co-brand's future success (Völckner and Sattler, 2006) and can impact consumers' perception (Simon and Ruth, 1998) and success of the co-brand (Xiao and Lee, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations